RANCANG BANGUN SISTEM INFORMASI PENJUALAN BAJU BERBASIS WEB - Handini Widyastuti; Juarni Siregar; Riswandi Ishak (Universitas Sahid Surakarta, 2020)
The main part of this final project is to create an e-commerce website at Syaunah Fashion store. Syaunah Fashion is a business store engaged in the sale of Muslim clothing. Syaunah Fashion does not have a product sales service through the internet or commonly referred to as e-commerce (Electronic Commerce). The store can only serve transactions made on the spot. And for the recording of customers who buy goods, until the storage of other data related to the sales process to report generation is still using the manual system. The method used by the authors in data collection for the title of Web-Based Sales Information System Design Syaunah Fashion Store using interviews. The supporting software used is Sublime Text and MySQL database. With the existence of web-based sales system, which has been connected with the database, facilitate the processing of sales transaction data with this computerized system helps in terms of product marketing, information will be provided to consumers can be faster, and also be the best solution to solve problems Is in this company.